Prospective evaluation of intraoperative intraocular lens stress fracture during cataract surgery. Issue 11 (November 2015) - Li, Bo; Lin, Tony; Tokarewicz, Alexander C.
Abstract : Purpose : To determine the incidence and risk factors of intraocular lens (IOL) stress fracture during cataract surgery. Setting : Ivey Eye Institute, London, Ontario, Canada. Design : Prospective, randomized cohort study. Methods : Patients scheduled for routine cataract surgery were randomized into 2 study groups. The 2 groups only differed in the use of Monarch IOL delivery cartridges for insertion of an Acrysof IQ SN60WF IOL. The cartridge C group used Monarch cartridge C, and the cartridge D group used Monarch cartridge D. Patients were examined for IOL stress fractures. Results : A total of 386 study eyes were enrolled. The overall incidence of IOL stress fracture was 6.22%. The incidence of IOL stress fracture with cartridge C and cartridge D groups were 3.16% and 9.18%, respectively ( P = .01). The IOL stress fracture rate for IOL power less than 18.0 D was 3.45%, IOL power between 18.0 D to 23.5 D was 6.49%, and IOL power over 23.5 D was 10.81%. A total of 24 IOL stress fractures were observed. Among IOL stress fractures, 45.8% were equal to or less than 1.0 mm in length. Two thirds of stress fractures were located over the central 4 mm of the IOL optic. No subjective adverse visual outcomes were reported from any of the observed IOL stress fractures. Conclusion : Intraocular lens stress fracture is recognizable risk during cataract surgery. Risk factors for IOL stress fracture include smaller IOL delivery cartridges and IOLs of higher refractive powers. There was a low risk for IOL stress fracture resulting in adverse subjective visual outcomes.